Impact of incluing a review stage within a software requirement development process - Simões, Rafael Pincegher; Carvalho, Livia Barroso; Calderado, Lais Girao da Silva; Silva, Robert Garcia da; Veras, Edluce Leitão; Souza, Daniel Augusto Rodrigues Lima de; Peres, Renan Clemente (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
The Android Open Source Project (AOSP) provides a lot of documentation and source code examples showing how to change characteristics of the operating system. Those characteristics allows device manufactures to create a new software with different requirements requested by various fonts, like carriers, integrated on the software. To improve the quality of software requirements developed by the team and thereby minimize the occurrence of errors, a review step was added in the internal software development process. This new step consists of reviewing the developed code and checking validations evidences performed on the implemented requirements. This work intent to evaluate the impact of this new step, both on the quality aspects of the implemented software and on the perspective of the team’s professionals regarding the improvement of the internal process. With this objective, the execution of process activities before and after the insertion of the new stage was evaluated, in the period from 2018 to 2023, and an internal survey was made, focused on understanding the relevance, perspective, advantages and disadvantages of this new step in the internal process. In general, it was possible to observe an improvement in the quality of the software developed by reducing errors made by developers. It was also possible to understand other matters, positive and negative, in the insertion of this new step based on the opinions collected in the survey. As future work we can verify the discussion about the possibility of automation in this step and the associated benefits.